Identification of resistance genes to Fusarium wilt in oil flax samples with different fatty acid composition - T. A. Rozhmina; A. V. Myasnikova (Аграрная наука Евро-Северо-Востока)
Oil flax seeds are valuable raw material for various industries. The purpose of the research was to form a genetic collection of oil flax for resistance to Fusarium wilt in order to create specialized varieties for various purposes with highly effective R-genes. On infectious backgrounds from populations of the fungus Fusarium oxysporum f. lini (Bolley) and highly virulent monoisolate No 39 of this pathogens, 28 promising genotypes of oilseed flax were assessed. Using a phytopathological test from the world gene pool of the species Linum usitatissimum L. 10 promising oil flax genotypes were identified – No. 3829, Uralsky (Russia), l. 6 AGT 1538, l. 12 AGT 987 (Czech Republic), Altess, Eole (France), Selectiong 3 (China), Arnu, Bison (USA) and Linda (Canada), which have effective resistance genes to the fungus F. oxysporum f. lini, differing in the fatty acid composition of the oil. Using the method of hybridological analysis, it has been established that resistance to Fusarium wilt in the low linolenic line l. 12 AGT 987 (Czech Republic) is determined by the Fu 11 gene, while in the high linolenic l. 3 Altess (France) it is Fu 4 (χ2 = 0.02…2.89). In the low linolenic line l. 6 AGT 1538 (Czech Republic) a previously unknown gene for resistance to this disease – Fu 12 was identified (χ2 = 0.0001…2.4100). The use of identified genetic sources in breeding programs will contribute to the creation of specialized varieties for the food, chemical and other industries with various R-genes of resistance, which will prevent the development of epiphytoties of this disease on oil flax.